Analisis Efektivitas Sistem Bagi Hasil Antara Pemilik Lahan Dan Petani Penggarap Di Kelurahan Pancaitana - Swasti, Tri Ika; Rayyani, Wa Ode (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
This study aims to analyze the effectiveness of the profit-sharing system between landowners and tenant farmers in Pancaitana sub-district. The research uses a descriptive qualitative method through interviews, observation, and documentation involving four informants. The findings show that the profit-sharing system is based on mutual agreement and trust, often carried out orally without a written contract. Two profit-sharing patterns were found: 1:1 when costs are shared, and 1:2 in favor of the cultivator when they bear all costs. The system aligns with Islamic economic principles, emphasizing justice, voluntarism, and mutual benefit. However, the absence of written agreements poses potential legal risks.